(untitled) (Revista Contexto & Saúde, 2025)
Objective: To assess the relationship between interleukin-6 (IL-6) polymorphism and the human papillomavirus (HPV) infection among women in a capital city in Northeastern Brazil. Methods: This cross-sectional study included sexually active women who received care through the public health system in São Luís, Maranhão State, Brazil. Information was collected on sociodemographic characteristics, sexual health, and number of pregnancies. Cytopathological analysis was performed using the Papanicolaou stain. HPV was detected using a nested polymerase chain reaction (PCR), and IL-6 −174G>C (rs1800795) polymorphism was detected by real-time PCR. For analysis of relationships with epidemiological and clinical data, patients were divided into two groups according to HPV status (HPV DNA-positive and -negative), and differences were deemed significant at p < 0.05. Results: The sample comprised 195 participants, 68 (34.88%) of whom were positive for HPV DNA. The prevalence of IL-6 −174G>C polymorphism was 28.72%, with 26.67% of patients exhibiting heterozygosity (GC) and 2.05% homozygosity (CC), indicating Hardy–Weinberg equilibrium. Conclusion: There was no association between IL6 −174G>C polymorphism and HPV status in the analyzed population. The findings of this study do not support the association between HPV DNA positivity and IL-6 −174G>C polymorphism among sexually active women in São Luís, Brazil.